2021
DOI: 10.1037/xan0000306
|View full text |Cite
|
Sign up to set email alerts
|

Where association ends. A review of associative learning in invertebrates, plants and protista, and a reflection on its limits.

Abstract: Since the beginning of the 21st century, the Minimal Cognition approach has emerged vigorously, focusing on the study of the adaptive behavior of the simplest organisms, including bacteria, assuming that they are sentient and information-processing entities. Although Minimal Cognition has occasionally used Pavlovian methods to try to demonstrate Associative Learning, neither the Psychology of Learning nor the Comparative Psychology traditions are prominent in the movement. However, the Psychology of Learning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 147 publications
(265 reference statements)
0
18
0
Order By: Relevance
“…It has been recently emphasized that the findings of some of the learning experiments that we rely upon in our paper are inconclusive because the experiments have yet to be repeated (seeLoy et al, 2021). Upon repeating these experiments, failure to replicate the same findings would of course count as evidence against ascribing certain forms of learning and memory to Physarum.…”
mentioning
confidence: 66%
“…It has been recently emphasized that the findings of some of the learning experiments that we rely upon in our paper are inconclusive because the experiments have yet to be repeated (seeLoy et al, 2021). Upon repeating these experiments, failure to replicate the same findings would of course count as evidence against ascribing certain forms of learning and memory to Physarum.…”
mentioning
confidence: 66%
“…Ample studies demonstrated associative (conditioning) learning in C. elegans ( Ardiel and Rankin, 2010 ; Cho et al, 2016 ; Kauffman et al, 2010 ; Loy et al, 2021 ; Oda et al, 2011 ; Sasakura and Mori, 2013 ). In this study, we systematically mapped each of the four types of associative memories (short- and long-term memories, each encoded using positive and negative associations) onto the compact neural network of C. elegans .…”
Section: Discussionmentioning
confidence: 99%
“…Though equipped with a small neural network, C. elegans can form both associative and non-associative memories ( Ardiel and Rankin, 2010 ; Loy et al, 2021 ; Sasakura and Mori, 2013 ). To form associative memories, worms are typically conditioned with a chemical (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, in that classi cation there are certain taxonomical mistakes. Some subphyla are confused with phyla, and more than twenty phyla were missing (Loy et al 2021). The taxonomical issue is important because, even though there is a case of a speci c species of a phylum in which a learning phenomenon has been demonstrated, it is not appropriate to generalize such results to the complete phyla, given the variability of each phylum.…”
Section: Introductionmentioning
confidence: 99%